A retrospective, descriptive study of patients evacuated to South Africa via an aero-medical provider from November 2010 to October 2011 - Odendaal, Salome Marlize (My University, 2017)
Background. When the medical needs of an ill or injured patient exceed what is available locally, urgent transportation to a well-equipped medical facility becomes prudent in order to minimize morbidity and mortality. Aircrafts are frequently used for this purpose. The aim. The aim of this study is to describe the patient profile of international aeromedical transportations (AMT) in sub-Saharan Africa. Methods. All air ambulance patient transportations performed by a South African based dedicated AMT provider, from 1 November 2010 to 31 October 2011, were reviewed and analysed. Results. Three hundred and six transportations were conducted of which 303 met the inclusion criteria. The patients’ ages ranged from 2 days to 86 years (median age 43 years). The top 3 nationalities transported were from South Africa (25.1%), United States of America (9.9%) and Angola (26%). The top 5 medical categories were trauma (23.4%), cardiology (16.2%), infective diseases (11.2%), neurology (10.9%) and surgery (9.6%). Malaria, as a single disease entity, contributed to 10.2% of all transportations. Transportations were mostly done from Angola (32.3%), Zambia (11.9%) and Mozambique (9.2%). Thirty one patients (10.2%) received mechanical ventilation, 16 (5.3%) inotrope and/or vasodilatory therapy, 68 (22.4%) oxygen and 2 (0.7%) were transported within a patient isolation unit. Conclusion. Transportation included neonatal, paediatric and geriatric patients with various medical conditions, some of whom required critical care procedures during AMT into South Africa. Therefore, the necessary skills training and appropriate equipment to care for critically ill patients and any possible complications should always be available during AMT.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Medicine in Emergency Medicine Johannesburg 2017.
Keywords: Air Ambulances; Transportation of Patients